Alcohol Consumption and Tryptophan Metabolism Among People with HIV Prior to Antiretroviral Therapy Initiation: The Uganda ARCH Cohort Study. (24th May 2021) - Pierre, Frantz; Forman, Leah S; Winter, Michael; Cheng, Debbie; Ngabirano, Christine; Emenyonu, Nneka; Hunt, Peter W; Huang, Yong; Muyindike, Winnie; Samet, Jeffrey; Hahn, Judith A; So-Armah, Kaku
Abstract: Aims: Alcohol is hypothesized to have effects on the kynurenine pathway of tryptophan catabolism, a potential mechanism for alcohol-induced depression and aggression. A biomarker of this pathway, the plasma kynurenine to tryptophan ratio (K/T ratio), has been associated with HIV progression, mortality and depression. Our aim was to assess whether hazardous alcohol consumption is associated higher K/T ratio among people with HIV. Methods: Participants were a subset of the Uganda Alcohol Research Collaboration on HIV/AIDS Cohort. Alcohol consumption was categorized (abstinent, moderate and hazardous alcohol use) using the Alcohol Use Disorders Identification Test—Consumption and phosphatidylethanol (PEth). K/T ratio was the primary outcome. We used linear regression adjusted for age, sex, FIB-4, hepatitis B surface antigen, log (HIV viral load) to estimate the association between alcohol consumption and K/T ratio. Results: Compared to abstinent participants, hazardous drinkers and moderate drinkers had higher K/T ratio but these differences did not reach statistical significance. Conclusions: Our results suggest that hazardous alcohol consumption, in the context of untreated HIV infection, may not significantly alter kynurenine to tryptophan ratio as a measure of activity of the kynurenine pathway of tryptophan metabolism. Abstract : Short Summary: Alcohol may alter the kynurenine pathway of tryptophan catabolism, a potential mechanism for alcohol-induced depression and aggression. Among Ugandans with HIV, neither hazardous nor moderate drinking, compared to abstaining from alcohol were associated with the kynurenine pathway of tryptophan catabolism.